Genetic evaluation of early growth in horro sheep under smallholder farm management, Oromia Regional State, Ethiopia - Tamiru Kibebew; Tesfaye Getachew; Kassahun Bekana Kitila; Gemeda Duguma Jaleta (PLoS ONE, 2026)
The study was conducted under on-farm management conditions in the Horro district of the Horro Guduru Wallaga zone in Oromia region. Flocks from the Community-Based Breeding Program (CBBP) were used for this study, which aimed to estimate genetic parameters for early growth traits. A total of 2,480 birth weight records, 2,441 three-month weight records, and 770 six-month weight records were analyzed. Least-squares means (LSM) analysis was performed using the General Linear Model (GLM) procedures of the Statistical Analysis System (SAS) to determine the effects of fixed factors. To estimate the (co) variance components and genetic parameters for growth traits, Restricted Maximum Likelihood (REML) procedures were implemented in the VCE 4.2.5 package. Multivariate genetic analysis was employed to estimate genetic correlations among traits. The least-squares means for birth weight (BWt), three-month weight (3MWt), and six-month weight (6MWt) were 2.72 ± 0.01, 12.33 ± 0.03, and 16.57 ± 0.07, respectively. The estimates of direct heritability obtained from the animal model were 0.16 ± 0.01, 0.19 ± 0.02, and 0.28 ± 0.35 for BWt, 3MWt, and 6MWt, respectively. The genetic correlations between BWt and 3MWt, BWt and 6MWt, and 3MWt and 6MWt were 0.30, 0.03, and 0.11, respectively. The moderate heritability estimates obtained for the growth traits indicate that genetic improvement through selection could lead to meaningful genetic change.